Cryopreservation of Canine Erythrocytes Using Dimethyl Sulfoxide, Polyethylene Glycol and Sucrose - Denysova Оlga; Zhegunov , Gennadiy (Problems of Cryobiology and Cryomedicine, 2021)
Cryoprotective properties of combined media of permeable (dimethyl sulfoxide) and impermeable (polyethylene glycol with m. w. 1500) cryoprotective agents during rapid cooling in liquid nitrogen of canine erythrocytes using saline and sucrose-saline media have been investigated. It was found that the use of combined solutions of cryoprotective agents based on polyethylene glycol with m.w. 1500 (15%) and dimethyl sulfoxide (2.5–10%) in saline was not quite effective for cryopreservation of canine erythrocytes. Reducing the salt concentration and adding cell-impermeable sucrose to the cryopreservation medium increase the preservation of erythrocytes after warming. The best cryoprotective properties for canine erythrocytes were demonstrated by 10% dimethyl sulfoxide based on sucrose-saline medium, with high preservation of cells after freeze-warming, mechanical and osmotic stability of warmed erythrocytes. This indicates the possibility of a long-term storage and use of cryopreserved canine erythrocytes for transfusions. Probl Cryobiol Cryomed 2021; 31(1): 038–050